Challenges for commercialization of university research for agricultural based invention - Yaakub N.I.; Wan Hussain W.M.H.; Abdul Rahman M.N.; Zainol Z.A.; Mujani W.K.; Jamsari E.A.; Sulaiman A.; Jusoff K. (2024)
Indexed by Scopus